Stúdium kvalitatívnych vlastností vybraných druhov rodu Echinacea Moench - Vaverková, S; Hollá, M; Tekel, J; Mistríková, I; Vozár, I (Ceska a Slovenska farmacie, 2001)
The paper examined the effect of production-technological conditions in relation to the ontogenetic stage of plants in three different species of the genus Echinacea Moench., comparing the species Echinacea purpurea, Echinacea atrorubens, and Echinacea pallida. It also examined the differences in the content of essential oil in different plant organs and evaluated the representation of individual components in the essential oils of the species under study at the stage of the optimal maturity for collection.
Keywords: Chromatography, Gas; chromatografie plynová; oleje prchavé; léčivé rostliny; Plant Extracts; Echinacea; Oils, Volatile; rostlinné extrakty; Plants, Medicinal; stavba rostlin; Plant Structures